Proceedings of the 16th ACM International Conference on Supporting Group Work - GROUP '10 2010
DOI: 10.1145/1880071.1880117
|View full text |Cite
|
Sign up to set email alerts
|

Towards building a productive, scalable and sustainable collaboration model for open educational resources

Abstract: This paper reports on a case study of a Health Open Educational Resources (OER) project in order to examine how to facilitate cross-institutional collaboration for OER production. This study assesses collaboration needs, identifies social and technical barriers, and builds a collaboration model to facilitate OER production. In doing so, we make three contributions to the GROUP community: (1) Whereas previous studies on distributed collaboration tend to focus on well-developed collaboration, in this study we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The works classified in the macro-theme "Production" highlight OER "production models", as the works of Luo, Ng'ambi, and Hanss (2010) and Khanna and Basak (2013) do; and different "life cycles", as approached by Glahn et al (2010), Hanna andWood (2011), Rennie, Johannesdottir, andKristinsdottir (2011) and Clements and Pawlowski (2012); "dissemination" as the paper of Lane and van Dorp (2011); and "creation and sharing" as the publication of Borthwick and Dickens (2013).…”
Section: Main Authors Abstract and Topics Addressed By The Publicationsmentioning
confidence: 99%
“…The works classified in the macro-theme "Production" highlight OER "production models", as the works of Luo, Ng'ambi, and Hanss (2010) and Khanna and Basak (2013) do; and different "life cycles", as approached by Glahn et al (2010), Hanna andWood (2011), Rennie, Johannesdottir, andKristinsdottir (2011) and Clements and Pawlowski (2012); "dissemination" as the paper of Lane and van Dorp (2011); and "creation and sharing" as the publication of Borthwick and Dickens (2013).…”
Section: Main Authors Abstract and Topics Addressed By The Publicationsmentioning
confidence: 99%
“…However, they highlight the potential for "cross-role, cross-institutional collaboration" around OER in sharing resources and practices. In response they argue that OER production and publishing infrastructures need to be developed within each organisation, extending Olson et al's work to suggest the need for "institutional dimensions of collaboration readiness" [12]. In this paper we analyse the results of this type of collaboration in a mature initiative, and explore the practices and phenomena that emerge.…”
Section: Open Educational Practicesmentioning
confidence: 80%
“…Even where a creation may be considered as the work of a single person, collaboration is essential in most creative tasks. Open practices can also provoke cross-cultural knowledge sharing [12], which has often been seen to inspire creativity, for example the influence of African art on Picasso and Matisse [5]. Group creativity needs to be understood as a process in which intersubjectivity plays a key role, as a process of "shared-meaning making" between those involved [22,23].…”
Section: Remixing and Reuse As Creative Collaborationmentioning
confidence: 99%
“…Because of the transparency of the design process, the partner universities reported that they felt they were considered equal partners, and there were rarely concerns about cultural imperialism. 16,17 Project planning: Understanding the effects of budget structures on collaborative work…”
Section: Design: Determining Mutually Beneficial Objectivesmentioning
confidence: 99%
“…17,18 Organizational autonomy and flexibility were shared values of all principal investigators. In Phases 2 and 3, each partner university had the freedom to determine how to allocate their tranche of the grant funds, with minor restrictions on the formats of budgets and on the activities themselves.…”
Section: Design: Determining Mutually Beneficial Objectivesmentioning
confidence: 99%